Changes in Antibiotic Prescription After Tooth Extraction: A Population-Based Study from 2002 to 2018 - Yoon Young Choi; Kyeong Hee Lee (Elsevier, 2021)
Objective: Microbial resistance due to antibiotic misuse is a worldwide problem. This study aimed to examine the trends in antibiotic prescription after tooth extraction in Korea. Methods: From the database of National Health Insurance Sharing Service, patients who underwent tooth extraction from 2002 to 2018 were selected as subjects, and 10% of them were selected via stratified sampling based on sex and age. Overall, 15,838,529 cases were observed for annual antibiotic prescription and broad-spectrum antibiotic prescription patterns. Additionally, standardized annual antibiotic use was calculated using a defined daily dose. Results: Prescriptions were issued in 13,429,770 (84.8%) of the tooth extraction cases, of which 12,179,185 (90.7%) included antibiotics. Logistic regression analysis revealed that the likelihood of prescribing antibiotics after tooth extraction decreased in 2003 compared to 2002 (odds ratio, 0.95) but increased from 2004 to 2018. In the case of the broad-spectrum antibiotic prescription rate, there was no clear trend between 2002 and 2012 (odds ratio, 0.89-1.07); however, over the last 5 years, the likelihood of broad-spectrum antibiotic prescription has steadily increased. The value of antibiotics based on the defined daily dose of 1000 patients per day was calculated to be 4.39 in 2002, exhibiting a steady increase later and reaching 6.97 in 2018, whereas that of broad-spectrum antibiotics was 1.68 in 2002 and has since been on the rise; the highest was 3.82 in 2018. Conclusions: Antibiotic use after tooth extraction increased over the last 17 years; additionally, the rate of prescribing broad-spectrum antibiotics has increased over the last 5 years.